Molecular characterisation of the "LEAome" in the resurrection plant Xerophyta humilis (Baker) - Waters, Robyn (Department of Molecular and Cell Biology, 2016)
Studies on resurrection plants and other anhydrobiotic organisms, have shown that Late Embryogenesis Abundant (LEA) proteins are expressed upon the onset of desiccation and are therefore inferred to be associated with the desiccation tolerance response. To date, despite some 25 years of research on these proteins, there is still very little understanding of the physiological function(s) of the majority of LEAs. This is because they lack tertiary structure in the hydrated state, making assigning of physiological roles difficult. This MSc study was undertaken to investigate the gene expression of a set of 21 putative LEAs during dehydration and subsequent rehydration stress, in the resurrection plant Xerophyta humilis (Baker). Recombinant proteins were expressed for 3 of the LEA genes from this set in order to perform structural studies and to ascertain their LEA status. These studies were conducted with the purpose of shedding light on the role of LEAs in desiccation tolerance, to add to the ever-growing transcriptomic and proteomic data, and to the current knowledge of these enigmatic proteins. Quantitative real-time gene expression (qPCR) analysis was conducted on the set of 21 full length X. humilis cDNA clone nucleotide sequences, with similarities to late embryogenesis mRNA sequences, derived from a study conducted by Collett et al., (2004). Expression analysis was conducted in both leaves and roots, across a dehydration and rehydration profile of X. humilis. Of this total group of 21 full length cDNA clones, three LEAs; XhLEA2-3 and XhLEA2-6 (two putative Group 2 LEA genes) and XhLEA3-5 (a putative Group 3 LEA gene), were chosen for cloning and expression studies. cDNAs of these XhLEAs were cloned into a modified bacterial expression vector and recombinant protein expression was attempted in E. coli.